Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1063/1.4799778
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of Fe doped, Co doped, and Fe+Co co-doped ZnO

Abstract: The structural, electronic and magnetic properties of Zn 0. 95 Results of these studies suggest that Fe and Co ions in the Fe+Co co-doped sample has a strong synergistic effect because they eliminated the presence of impurities and gave the strongest ferromagnetic signal. Possible role of charge transfer ferromagnetism involving mixed valence ions is considered as a potential mechanism in these nanoparticles. Presence of both Co 2+ and Fe 3+ might promote more efficient charge transfer in the co-doped Zn 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…7 shows a wasp-waist M-H plots (at 300 o C) which might have been observed due to hole mediated exchange interaction [4]. Ferromagnetic behaviour arises here due to introduction of hole by the exchange of Co 2+ ions with Zn site in Co doped ZnO [26]. Because of appearance of hole charge transfer results in additional charge from the dopant, which results in magneto-electronic coupling.…”
Section: Introductionmentioning
confidence: 92%
“…7 shows a wasp-waist M-H plots (at 300 o C) which might have been observed due to hole mediated exchange interaction [4]. Ferromagnetic behaviour arises here due to introduction of hole by the exchange of Co 2+ ions with Zn site in Co doped ZnO [26]. Because of appearance of hole charge transfer results in additional charge from the dopant, which results in magneto-electronic coupling.…”
Section: Introductionmentioning
confidence: 92%
“…It is worth mentioning that, in a stoichiometric wurtzite structure, the c/a ratio is 1.633. Here, all of the samples showed a significantly smaller c/a ratio (1.601±0.001), and this might indicate the presence of V O and extended defects [19]. As for the ZF2 samples annealed at different T A , the lattice parameters and the cell volume of the ZF2-600 and ZF-700 samples are higher than those of the ZF2-500 sample, as shown in Table 1.…”
Section: A X-ray Diffraction Analysismentioning
confidence: 77%
“…It was established that the observed ferromagnetic effect was related to the mutual substitution of Zn 2+ and Co 2+ ions in the lattice sites of ZnO grains. Li doped sam ples exhibited only paramagnetic properties, but a combination of Li and Co increased the saturation magnetization from 7.1 to 9.5 G. Experimental study [24] of the nanodispersed structures with composi tions ZnO 0.95 Co 0.05 O, ZnO 0.95 Fe 0.05 O, and ZnO 0.9 Co 0.05 Fe 0.05 O obtained by the sol-gel method showed that the simultaneous doping with two metal ions (Co 2+ , Fe 2+ ) led to several fold increase in the manifestation of ferromagnetic properties.…”
Section: Ferromagnetism Of Varistor Ceramicsmentioning
confidence: 89%